Control of the servo motor using feedback linearization and artificial gorilla troops optimizer - Jovanović, Radiša; Vesović, Mitra (Nonlinear Analysis: Modelling and Control, 2025)
This paper establishes a nonlinear optimization strategy for position control of a direct current motor. When experimental evidence showed that the linear model does not sufficiently represent the system, the model is modified from linear to nonlinear, using friction-induced nonlinearity. In the course of the research, an analysis of the nonlinear feedback linearizing controller and the up to date gorilla troops optimization algorithm are carried out. The proposed algorithm is juxtapose with four others metaheuristic optimizations. Furthermore, performances with and without different types of disturbances are compared for individual desired output signals. The experimental results corroborate the nonlinear control’s robustness.